Additive manufacture of low melting point metal porous materials: Capabilities, potential applications and challenges. (October 2021) - Gao, Jian-Ye; Chen, Sen; Liu, Tian-Ying; Ye, Jiao; Liu, Jing
Graphical abstract: Abstract: Low melting point metals (LMPMs) represent a class of emerging multi-functional metal materials with melting points below 300 °C. As a novel branch of LMPM materials, the LMPM-based porous materials (LMPM-PMs) perfectly combine the fundamental characteristics of LMPMs and porous structure together. Compared with conventional porous metal materials, LMPM-PMs appear much easier to achieve additive manufacturing (AM) at room temperature due to their low cohesive energy. Besides, the porous structure of the LMPM-PMs is prone to be regulated and controlled by their surface tension properties and external field, such as thermal field, electric field and magnetic field, via a transformable way, which promises it with outstanding reconfigurable characteristics and diversified values. Here, we systematically summarize and prospect the additive manufacture of LMPM-PMs from the category of the capabilities, future practices, and potential challenges. Firstly, the fundamentals about LMPMs and related studies over the past few years are briefly reviewed, aiming at providing readers with a general sense about LMPMs, as well as serving guidance for the increasing coming use of LMPM-PMs. Then, the AM of LMPM-PMs is comprehensively illustrated from five parts: preparation and modification of LMPM powder, fabrication of LMPM-PMs, conceptual LMPM-PM based AM, surface modification, mechanical properties of LMPM-PMs. Following that, the unique capacities of LMPM-PMs are outlined. The potential applications and significance of LMPM-PMs are clarified based on the fundamental research on LMPMs. Finally, a perspective interpretation of the potentials and challenges of LMPM-PMs is given.